Maqashid sharia and corporate sustainability under financial vulnerability - Linda Ayu Wulandari; Hendro Paulus; Shinta Melzatia; Lin Oktris; Taufik Akbar (Indonesia Auditing Research Journal, 2026)
This study examines the effect of CSR, Islamic CSR, and environmental quality on corporate performance, measured by profitability and growth, with financial vulnerability as a moderating variable. This research will conduct with Moderated Regression Analysis of panel data from 108 observations basic material entities achieving PROPER on 2021-2024 by Ministry of Environment and Forestry of Indonesia Republic, which Islamic CSR is measured using a GRI-Maqasid Index, CSR using the GRI Standards 2021, and financial vulnerability with DER, use EViews 13. The results show that CSR and Islamic CSR positively affect profitability but do not significantly firm growth. In contrast, environmental quality negatively affects short-term profitability yet supports growth. Financial vulnerability moderates these relationships by weakening the profitability effects of CSR and ICSR, while also reducing the positive influence of environmental quality on corporate growth. The findings highlight aligning ethical, social, and environmental strategies grounded in Maqasid Sharia with financial conditions to sustain long term corporate performance. This study compares Islamic CSR and CSR in a single framework, using profitability and growth as well as financial vulnerability, revealing the role of ethical orientation and financial constraints on long term corporate performance.